2011
DOI: 10.3109/03630269.2011.621007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hemoglobinopathies in Rural Bengal, India

Abstract: India is in the thalassemia belt of the world. Both α- and β-thalassemia (α- and β-thal) are found in West Bengal, a state in the eastern part of India. There was no systematic large published study to investigate the prevalence rates of different hemoglobinopathies in West Bengal. This study was conducted in school and college students, newly married couples and pregnant women after proper counseling in the rural areas of five districts of West Bengal state in eastern India. Thalassemia testing was done using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 1 publication
(1 reference statement)
1
31
2
1
Order By: Relevance
“…Sachdev et al [26] , Jain et al [30] and Mukhopadhyay et al [29] found 12.57%, 29.3 % and 14.5% abnormal hemoglobin fractions respectively. Sachdev et al [26] , Rao et al [27] , Dolai et al [28] and Mukhopadhyay et al [29] found beta thalassemia trait cases to be 8.9 %,18.1 %,10.38 % and 5.6 % respectively. Our findings are comparable to these different Indian studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sachdev et al [26] , Jain et al [30] and Mukhopadhyay et al [29] found 12.57%, 29.3 % and 14.5% abnormal hemoglobin fractions respectively. Sachdev et al [26] , Rao et al [27] , Dolai et al [28] and Mukhopadhyay et al [29] found beta thalassemia trait cases to be 8.9 %,18.1 %,10.38 % and 5.6 % respectively. Our findings are comparable to these different Indian studies.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies by Sachdev et al [26] , Rao et al [27] , Dolai et al [28] and Mukhopadhyay et al [29] have taken 2600, 800, 35413 and 10407 cases respectively for their study. Sachdev et al [26] , Jain et al [30] and Mukhopadhyay et al [29] found 12.57%, 29.3 % and 14.5% abnormal hemoglobin fractions respectively.…”
Section: Discussionmentioning
confidence: 99%
“…As the prevalence of thalassemia varies with different geographical areas of India. 1,2,7,8 we took the prevalence of 66.7% among the six ethnic groups from Assam 6 while calculating the sample size. Taking relative error of 5% of prevalence, the sample size calculated was 800 cases.…”
Section: Methodsmentioning
confidence: 99%
“…1,2 In different parts of India, the incidence of haemoglobinopathies also differs. In Orissa, HbS is common 7 whereas in West Bengal the commonest one is HbE. 8 ICMR multicenter study showed that HbE trait was mainly seen in Kolkata in West Bengal (3.92%) and in Dibrugarh in Assam (23.9%).…”
Section: Introductionmentioning
confidence: 99%
“…6 The problem is worse in the state of West Bengal where the prevalence of beta thalassemia carriers is estimated to be 10.38%, with another 4.30% being Hemoglobin E [ 26(B8)Glu Lys] carriers. 7 IHTM alone has 1410 registered thalassemics with 72% of them suffering from Hemoglobin E beta thalassemia. A percentage of 99.8 of these patients have been categorized by the government as living below the poverty line.…”
Section: Introductionmentioning
confidence: 99%